Male and female English students’ perspectives in English speaking class activities - Adi F Mahmud; Adamu M Babikkoi (Center for Humanities and Innovation Studies, 2018)
This research aims to investigate male and female English students’ perspectives in English speaking class activities. This research applied qualitative approach with the descriptive qualitative design. Unstructured interview technique used to collect the data of this study. The researcher interviewed ten participants who consist of five male and five female at English students of Universitas Muhammadiyah Maluku Utara. The participants are from the third semester to the fifth semester who have joined English speaking class activities. In analyzing data, the researcher followed three steps consists of reading/memoing, describing, and classifying. In the Reading/memoing step, the researcher transcribed all results of the interview from the recorder and read transcription to catch the initial sense of data. The describing step lead the researcher to develop the thorough and comprehensive description of participants, setting, and the phenomenon of the research to cover the rich complexity of the research. In classifying stage, the research made the research data and brooked it down into a smaller unit, put the appropriate unit together in more general and analytic form. Results showed that there are four main perspectives revealed by students (1) language used by a lecturer in English speaking activities, (2) learning approaches, (3) learning strategies, and (4) learning the place. Then, male and female students’ stated similar perspectives, (2) Male and female students’ perspectives do not in line with lecturers perspectives in English speaking class activities.